Sequence analysis of cell-free DNA derived from cultured human bone osteosarcoma (143B) cells - Abel Jacobus Bronkhorst; Johannes F Wentzel; Vida Ungerer; Dimetrie L Peters; Janine Aucamp; Etienne Pierre de Villiers; Stefan Holdenrieder; Piet J Pretorius (Tumor Biology)
The true importance of cell-free DNA in human biology, together with the potential scale of its clinical utility, is tarnished by a lack of understanding of its composition and origin. In investigating the cell-free DNA present in the growth medium of cultured 143B cells, we previously demonstrated that the majority of cell-free DNA is neither a product of apoptosis nor necrosis. In the present study, we investigated the composition and origin of this cell-free DNA population using next-generation sequencing. We found that the cell-free DNA comprises mainly of repetitive DNA, including α-satellite DNA, mini satellites, and transposons that are currently active or exhibit the capacity to become reactivated. A significant portion of these cell-free DNA fragments originates from specific chromosomes, especially chromosomes 1 and 9. In healthy adult somatic cells, the centromeric and pericentromeric regions of these chromosomes are normally densely methylated. However, in many cancer types, these regions are preferentially hypomethylated. This can lead to double-stranded DNA breaks or it can directly impair the formation of proper kinetochore structures. This type of chromosomal instability is a precursor to the formation of nuclear anomalies, including lagging chromosomes and anaphase bridges. DNA fragments derived from these structures can recruit their own nuclear envelope and form secondary nuclear structures known as micronuclei, which can localize to the nuclear periphery and bud out from the membrane. We postulate that the majority of cell-free DNA present in the growth medium of cultured 143B cells originates from these micronuclei.